2020
DOI: 10.1038/s41467-020-17545-2
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2 signaling drives meningeal vascular regeneration upon head injury

Abstract: Upon severe head injury (HI), blood vessels of the meninges and brain parenchyma are inevitably damaged. While limited vascular regeneration of the injured brain has been studied extensively, our understanding of meningeal vascular regeneration following head injury is quite limited. Here, we identify key pathways governing meningeal vascular regeneration following HI. Rapid and complete vascular regeneration in the meninges is predominantly driven by VEGFR2 signaling. Substantial increase of VEGFR2 is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…We found that some of the ECs in the tumor had high proliferative potential; thus, given the lack of cancer cell growth in our model, human blood vessels are maintained depending on non-cancer cell-derived VEGF in this cranial window model. Further analysis of the origin of this VEGF is required; however, it is apparent that our method differs significantly from previous reports on the growth of human blood vessels in vivo In a recent study, Koh et al showed that dura mater ECs had more angiogenic potential than brain ECs, and that VEGFR2 signaling in the dura mater promoted vascular regeneration in an experimental head injury model 23 . Considering these results, damage to the dura mater caused by tumor transplantation may promote VEGF-dependent EC sprouting.…”
Section: Discussionmentioning
confidence: 90%
“…We found that some of the ECs in the tumor had high proliferative potential; thus, given the lack of cancer cell growth in our model, human blood vessels are maintained depending on non-cancer cell-derived VEGF in this cranial window model. Further analysis of the origin of this VEGF is required; however, it is apparent that our method differs significantly from previous reports on the growth of human blood vessels in vivo In a recent study, Koh et al showed that dura mater ECs had more angiogenic potential than brain ECs, and that VEGFR2 signaling in the dura mater promoted vascular regeneration in an experimental head injury model 23 . Considering these results, damage to the dura mater caused by tumor transplantation may promote VEGF-dependent EC sprouting.…”
Section: Discussionmentioning
confidence: 90%
“…Pericytes are specialized mural cells that stabilize capillaries as part of the neurovascular unit and comprise a vital part of the BBB by regulating the integration between astrocytes and endothelial cells (Armulik et al , 2010). Moreover, NG2 + ‐pericytes have been shown to play a vital role in the stabilization and structure of blood vessels after brain injury, which has been correlated with pAKT upregulation in recovering blood vessels (Teichert et al , 2017; Koh et al , 2020). We examined the morphology of NG2 + ‐pericytes and their association with the CD31 + vasculature as a measure of BBB integrity (Hartmann et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…KEGG analysis and GSEA enrichment analysis showed that the significantly enriched pathways were PI3K-Akt and VEGF signaling pathways. VEGFR-2 , also known as KDR promotes vascular regeneration [ 73 ]. Cartilage Oligomeric Matrix Protein ( COMP ) binds smad protein and upregulates BMP-2 which induces intracellular signal, ultimately increasing the expression of BMP receptor thus regulating bone regeneration [ 74 ].…”
Section: Discussionmentioning
confidence: 99%